2018
DOI: 10.1016/j.chempr.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Doped Graphene Catalyzes Dinitrogen Fixation with Electricity

Abstract: The development of catalysts for electrochemical dinitrogen reduction has so far focused on metal-based compounds and materials. In a recent report published in Joule, Zheng and colleagues demonstrated that boron-doped graphene electrochemically reduces dinitrogen in aqueous solution under ambient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In addition to N, the effects of other dopants, such as S, 20,24 B, 101 and dual‐element dopants, such as B‐N 28 and N‐P 29 , on the production rate have also been discussed. However, the understanding of the configurations for the active moieties in these heteroatom‐doped carbon catalysts is still not enough.…”
Section: Effects Of Electrocatalyst/electrolyte Interface On the Production Rate Of Ammoniamentioning
confidence: 99%
“…In addition to N, the effects of other dopants, such as S, 20,24 B, 101 and dual‐element dopants, such as B‐N 28 and N‐P 29 , on the production rate have also been discussed. However, the understanding of the configurations for the active moieties in these heteroatom‐doped carbon catalysts is still not enough.…”
Section: Effects Of Electrocatalyst/electrolyte Interface On the Production Rate Of Ammoniamentioning
confidence: 99%
“…The introduction of defects into electrocatalysts can effectively enhance the catalytic performance. [67][68][69] In terms of graphene, its defects can be divided into two categories: extrinsic defects (heteroatoms) and intrinsic defects (edge, vacancy, and dislocation defects). [70] Up to now, several works have shown that the introduction of intrinsic defects onto graphene can effectively enhance the NRR performance.…”
Section: Graphene With Intrinsic Defectsmentioning
confidence: 99%
“…The excellent physical, electronic, and chemical properties of two-dimensional (2D) materials have attracted extensive scientific research [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. In addition, 2D materials, such as molybdenum disulfide, graphene, and metal–organic frameworks (MOFs) [ 14 , 15 , 16 ], have emerged as potential candidates for electrochemical nitrogen reduction reactions (NRRs). Notably, MXene, a new member of the 2D material family that joined in 2011 [ 17 ], has developed rapidly in the past nine years [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%